Pengaruh Konsumsi Ekstrak Daun Katuk Dan Ekstrak Daun Kelor Terhadap Peningkatan Produksi ASI Di Wilayah Kerja Puskesmas Kebonagung - Ardhita Listya Fitriani (Midwifery Care Journal, 2023)
ABSTRACTHealth profile Central Java Province The percentage of exclusive breastfeeding for babies 0-6 months in Central Java, in 2019 was 66.0 percent, an increase compared to the percentage of exclusive breastfeeding in 2018, which was 65.6 percent. Meanwhile, data for the city of Demak who were exclusively breastfed in 2019, there were 219 babies aged 0-6 months with a percentage of 78.4%. Low milk production caused failure of breastfeeding for babies. One of the efforts to increase milk production is consuming katuk leaf extract and moringa leaf extract. Research Objectives: To determine the Effectiveness of Consumption of Katuk Leaf Extract and Moringa Leaf Extract on Increasing Breast Milk Production in the Working Area of the Kebonagung Health Center. Research Methods: This type of quasi-experimental research. The research design used a two group pretest posttest design. The research population is mother as much as 21 respondents. The number of samples is 18 respondents. The sampling technique is purposive sampling. Research Results: There is no Effectiveness of Consumption of Katuk Leaf Extract and Moringa Leaf Extract on Increasing Breast Milk Production in the Working Area of the Kebonagung Health Center (P-value 0.737). Suggestion: as a guide in providing professional midwifery care, especially for breast milk production patients who do not intervene enough to consume Katuk Leaf Extract and Moringa Leaf Extract.. Keywords: Katuk Leaf Extract, Moringa Leaf Extract, Breast Milk Production